Cosmic ray contributions from rapidly rotating stellar mass black holes: cosmic Ray GeV to EeV proton and anti-proton sources - Allen, M.; Biermann, P. L.; Chieffi, A.; Chini, R.; Frekers, D.; Gergely, L.; Gopal-Krishna,; Harms, B.; Jaroschewski, I.; Joshi, P. S.; Kronberg, P. P.; Kun, E.; et al. (Frontiers in Astronomy and Space Sciences, 2024)
In Radio Super Novae (RSNe) a magnetic field of (B × r) = 1016.0±0.12 Gauss × cm is observed; these are the same numbers for Blue Super Giant (BSG) star explosions as for Red Super Giant (RSG) star explosions, despite their very different wind properties. The EHT data for M87 as well for low power radio galaxies all show consistency with just this value of the quantity (B × r), key for angular momentum and energy transport, and can be derived from the radio jet data. We interpret this as a property of the near surroundings of a black hole (BH) at near maximal rotation, independent of BH mass. In the commonly used green onion model, in which a 2 π flow changes over to a jet flow we interpret this as a wind emanating from the BH/accretion disk system and its surroundings. Near the BH collisions in the wind can produce a large fraction of anti-protons. In this scenario the cosmic Ray (CR) population from the wind/jet is proposed to be visible as EeV protons and anti-protons in the CR data to EeV energy, with a E−7/3 spectrum. This can be connected to a concept of inner and outer Penrose zones in the ergo-region. The observed numbers for the magnetic field imply the Planck time as the governing time scale: A BH rotating near maximum can accept a proton per log bin of energy in an extended spectrum with the associated pions every Planck time.